(untitled) - Gerald Abraham (1904- (Oxford, New York, 1993)
The book provides a comprehensive history of music from its origins in the ancient world up to the death of Stravinsky. In addition to a full account of the development of Western music, which includes information on composers, their works, and their influences, the book also interweaves chapters on the musical traditions of other parts of the world
Keywords: music - history and criticism